INSTITUTIONAL ECONOMIC PERSPECTIVE ON GOVERNMENT SYSTEM MATURITY LEVEL INDONESIAN ELECTRONIC BASED 2023 - Widnyani, Ida Ayu Putu Sri; Sirna, I Ketut; Patni, Ni Luh Putu Suarmi Sri; Tingkes, I (Department of Government, FISIP, Universitas Padjadjaran, 2024)
This research aims to analyze the maturity level of Electronic-Based Government Systems, both at the National, Central and Provincial Levels in 2022 using quantitative data sourced from the Decree of the Minister for Empowerment of State Apparatus and Bureaucratic Reform Number 108, 2023 concerning Results of Monitoring and Evaluation of Results Electronic Based Government. The quantitative data analysis technique used is descriptive statistical techniques, while the evaluation technique covers four SPBE domains, eight SPBE aspects, and forty-seven SPBE indicators. The research results show that the SPBE maturity level at the national level is 2.40, at the central level is 2.49 and at the provincial level is 2.37. The three SPBE indices show that the Indonesian SPBE process is at the managed level, while the SPBE service is at the interaction level. This means that both the managed level and the interaction level show that Indonesia's SPBE is still far from the optimal level. Based on these findings, it can be recommended to policy makers that economic institutions as a value and bureaucratic reform as a modern organization are more optimized in their implementation.gb777